Deskripsi dan Karakteristik Morfometri Kambing Peranakan Etawa yang Terintegrasi dengan Tanaman Lada - Setiawan, Duta (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
The integration system for Peranakan Ettawa (PE) goat livestock and pepper plants is one model for developing PE goat cultivation to increase agricultural businesses' efficiency and productivity. The research aims to determine the description of breeder characteristics in implementing the integration of PE goats and pepper plants, grazing capacity, and morphometric measurements on the bodies of PE goats in Bengkayang Regency. The research was conducted in the Selebar sub-district of Bengkayang Regency using survey and interview methods. The breeders were determined purposively using the criteria that the livestock group would still run an integrated PE goat farming business with pepper plants. Analyze breeder characteristics and morphometric data descriptively to determine the relationship between the grazing capacity of PE-integrated goats with pepper plants and livestock units (ST) calculated using linear regression. The research results describe PE goat breeders who are integrated with pepper plants based on age at the productive age of 41-50 years and experience in raising PE goats for 11-20 years. The grazing capacity of PE goat breeders is 32.71 Kg with an R2 of 94.93%. The morphometry of male and female PE goats aged around two integrated with pepper plants in Selebar District is not much different from SNI 7352.1, so it is still good for improving their performance.